2020
DOI: 10.1504/ijemr.2020.106430
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the impact of atmospherics and online flow cues on visiting intentions: the case of Jordan' virtual tourist centre

Abstract: Using the stimulus-organism-response (S-O-R) framework, this study aims to investigate the impact of atmospherics and online flow cues of Jordan virtual tourist centre on visitors' affective and cognitive states, which are assumed to affect their visiting intentions. This is based on the fact that more tourists are getting information directly via the internet to direct their choices of tourism destinations. In order to test our proposed model, an online survey was launched via different social networking mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Cultural and heritage tourism experiences can be created using virtual reality needs. The study uses multi-method explorative research, personas and scenarios are developed to inform the subsequent co-design of virtual reality solutions along the visitors' journey [31]. However, virtual reality is based on the visitor intentions they perceive from the different social networking sites.…”
Section: Virtual Realitymentioning
confidence: 99%
See 1 more Smart Citation
“…Cultural and heritage tourism experiences can be created using virtual reality needs. The study uses multi-method explorative research, personas and scenarios are developed to inform the subsequent co-design of virtual reality solutions along the visitors' journey [31]. However, virtual reality is based on the visitor intentions they perceive from the different social networking sites.…”
Section: Virtual Realitymentioning
confidence: 99%
“…Destination marketing using the augmented reality and virtual reality experience needs social media marketing to engage the users with these technologies. For example, users may argue their mobile at a restaurant, instantly provide reviews or menus, or aim their tablet at a historic landmark and be presented with information about its history [31]. Coghlan & Carter (2020) [39] conducted the study using the Design-Play-Experience Model's gaming conceptual framework and to find the interactions with the game.…”
Section: Augmented Reality and Social Media Tourismmentioning
confidence: 99%
“…With regards to low and high-task-relevant atmospherics, Shatnawi, Ashour, and Kakeesh (2020) have identified that an improve in layout design, information quality and visual appearance are positively affecting consumers' visit intention. Although this research is founded on a tourism website case study, these findings can easily be extended to the fashion industry when considering similar findings from other researchers.…”
Section: Visual Atmosphericsmentioning
confidence: 99%
“…Profits typically result from several investments (Goovaerts et al 2014). Improving IMC, services, and the organizational aspects of city marketing can result in substantially increased investment in the city (Shatnawi et al 2020). Such investments can then yield more profit and income-generating activities over time (Al-Weshah 2017).…”
mentioning
confidence: 99%